2019
DOI: 10.1111/bjh.15759
|View full text |Cite
|
Sign up to set email alerts
|

Methodological aspects of health‐related quality of life measurement and analysis in patients with multiple myeloma

Abstract: Summary Multiple myeloma (MM) is an incurable but treatment‐sensitive cancer. For most patients, this means treatment with multiple lines of anti‐myeloma therapy and a life with disease‐ and treatment‐related symptoms and complications. Health‐related quality of life (HRQoL) issues play an important role in treatment decision‐making. Methodological challenges in longitudinal HRQoL measurements and analyses have been identified, including non‐responses (NR) to scheduled questionnaires. Publications were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 96 publications
(132 reference statements)
0
5
1
Order By: Relevance
“…Those strategies resulted in a very high PRO completion rate of 95%, with just 5% non-response. PRO completion rates in longitudinal studies of patients with MM are often not reported, and of the studies, where this information was reported, the PRO completion rate was 78-98% [53]. Only one study has reported a higher PRO completion rate compared to our findings.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Those strategies resulted in a very high PRO completion rate of 95%, with just 5% non-response. PRO completion rates in longitudinal studies of patients with MM are often not reported, and of the studies, where this information was reported, the PRO completion rate was 78-98% [53]. Only one study has reported a higher PRO completion rate compared to our findings.…”
Section: Discussioncontrasting
confidence: 61%
“…Methodological considerations concerning PRO assessment time points were included as part of the study planning. Clinical visits are frequently chosen time points for PRO assessment in clinical trials of MM patients [53]. This decision has the advantage of reducing the risk of NR, since patients have the opportunity to complete the questionnaires at the hospital with assistance from the study nurse.…”
Section: Discussionmentioning
confidence: 99%
“…Dimensions are described by the arithmetic mean and standard deviation. As suggested by Nielsen et al 22. Mann-Whitney U test was used to compare the dimensions within two groups (gender, treatment).…”
Section: Methodsmentioning
confidence: 99%
“…The Danish prospective, nation-wide, observational survey (QoL-MM) [20] framed our study. The study population was a subpopulation of the QoL-MM cohort referred to as QoL-MM-C19.…”
Section: Study Design and Populationmentioning
confidence: 99%